2021
DOI: 10.1111/ced.14731
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of papulopustular rosacea and comparison of dermoscopic features in patients with or without concomitant Demodex folliculorum

Abstract: Background. The dermoscopic findings of papulopustular rosacea include tiny papules and pustules, follicular plugs and follicular dilatation. Demodex tails and Demodex follicular openings are dermoscopic indicators that are mainly found in primary demodicosis and, less frequently, in rosacea. Aim. To describe the dermoscopic features of papulopustular rosacea and to investigate the differential dermoscopic features between patients with and without concomitant Demodex infestation. Methods. We conducted a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…This difference might be caused by the sample size. Additionally, follicular findings were more prominent in PPR compared with ETR, consistent with previous reports [12,15,22] . A previous study indicated that follicular scales (included as yellow scales in the present study) should be regarded as a diagnostic criterion for rosacea since they were statistically correlated with persistent erythema [23] .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This difference might be caused by the sample size. Additionally, follicular findings were more prominent in PPR compared with ETR, consistent with previous reports [12,15,22] . A previous study indicated that follicular scales (included as yellow scales in the present study) should be regarded as a diagnostic criterion for rosacea since they were statistically correlated with persistent erythema [23] .…”
Section: Discussionsupporting
confidence: 91%
“…Most plugs were yellow and corresponded to keratotic material and/or sebum in dilated follicular infundibula. [ 12 ] Lallas [ 10 ] suggested that the presence of orange-yellowish areas implied granulomatous rosacea (GR). This feature was detected for all subtypes in our current study, indicating that some GR cases might experience missed or delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations